Neutrophil to Lymphocyte Ratio as a Predictor of Restenosis After Angioplasty and Stenting for Asymptomatic Carotid Stenosis. (February 2019) - Dai, Zhengze; Li, Rongrong; Zhao, Nan; Han, Yunfei; Wang, Mengmeng; Zhang, Shuai; Bai, Yongjie; Li, Zibao; Liang, Meng; Xiao, Lulu; Ma, Minmin; Liu, Xinfeng; et al.
The inflammatory response plays a vital role in the development of in-stent restenosis (ISR) after carotid angioplasty and stenting (CAS). The neutrophil to lymphocyte ratio (NLR) has been suggested as a sensitive inflammatory marker. We explored the association between NLR and ISR in CAS patients. A total of 427 patients who underwent CAS were enrolled. Neutrophil to lymphocyte ratio was measured before the procedure. Clinical examination and radiographic evaluation were performed at 6 months and annually after the procedure. In-stent restenosis was defined as ≥50% stenosis in the treated lesion. Cox regression was used to identify predictors of ISR after CAS. Of the 459 arteries (in 427 patients) with CAS, 72 (15.7%) were identified with ISR during a mean follow-up of 14.6 (19.1) months (range, 0.7-120.7 months). Increased NLR (≥2.13) was significantly related to ISR in patients with asymptomatic stenosis ( P = .001). However, significance was not observed in symptomatic stenosis. On multivariate analysis, baseline NLR ≥ 2.13 (hazard ratio [HR], 2.74; 95% confidence interval [CI], 1.46-5.14), smoking (HR, 1.99; 95% CI, 1.11-3.58), residual stenosis (HR, 1.12; 95% CI, 1.09-1.15), and baseline glucose level (HR, 1.01; 95% CI, 1.01-1.02) were associated with ISR. Elevated NLR may be a predictor of ISR after CAS for asymptomatic stenosis.